2019
DOI: 10.1007/s00187-019-00279-8
|View full text |Cite
|
Sign up to set email alerts
|

Controlling for sustainability strategies: findings from research and directions for the future

Abstract: Over the past decade the focus of sustainability researchers has broadened to explore management controls for sustainable business practice. This paper contributes to the emerging area of interest on understanding the roles management controls play by presenting a review of the literature that specifically focuses on the relationship between management controls and sustainability strategies. The paper shows that the current literature predominantly focuses on exploring controls from a management control design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(59 citation statements)
references
References 92 publications
2
57
0
Order By: Relevance
“…Since the financial crisis of 2008/09, many reform initiatives on sustainable corporate governance and sustainable management control were discussed and finalised from an international perspective (e.g., Feder and Weißenberger 2019;Ghosh et al 2019;Johnstone 2019;Lingnau et al 2019). Boards of directors are motivated to engage in implementing a sustainability management system and increasing their sustainability expertise.…”
Section: Discussion and Contributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the financial crisis of 2008/09, many reform initiatives on sustainable corporate governance and sustainable management control were discussed and finalised from an international perspective (e.g., Feder and Weißenberger 2019;Ghosh et al 2019;Johnstone 2019;Lingnau et al 2019). Boards of directors are motivated to engage in implementing a sustainability management system and increasing their sustainability expertise.…”
Section: Discussion and Contributionsmentioning
confidence: 99%
“…Regarding increased research on business case(s) for CSR (Reinhardt et al 2020;Salzmann et al 2005), firm value substantially may be affected negatively through damage to firm reputation as a consequence of corporate irresponsibility. Sustainable management control regarding CSR-related board expertise represents a strategy to decrease conflicts of interest between management and different stakeholder groups, and to strengthen firm reputation (e.g., Feder and Weißenberger 2019;Ghosh et al 2019;Johnstone 2019;Lingnau et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…It is interesting to note that our review of the literature also stresses MFCA's role for strategic decisions, which had not been made explicitly by ISO [13]. Strategic decision-making plays a pivotal role in an organization due to its long-term effects [82] and therefore has also been widely addressed in the literature of accounting and control for sustainability strategy [83]. In various studies of our sample, it is shown how MFCA can support managers in ensuring the future sustainability of an organization (e.g., implementing cleaner production processes) [52,61,74].…”
Section: Benefits Of Mfca Application In Developing Countriesmentioning
confidence: 99%
“…Similarly, studies related to the use of MCSs for sustainability and CSR have been conducted to identify how companies use MCSs and/or SCSs in their sustainability and CSR practices (Crutzen et al, 2017;Durden, 2008;Riccaboni and Leone, 2010). Some scholars have argued that formal and informal controls need to reinforce one another to promote sustainability and CSR objectives internally, while others discuss the primacy of informal controls negating the need for formal controls (Crutzen, 2017;Ghosh et al, 2019). Control congruity or primacy is based on research undertaken on a limited number of organizations (Ghosh et al, 2019).…”
Section: Introductionmentioning
confidence: 99%